Innovación tecnológica para el desarrollo de los emprendimientos sociales - Espinosa Vera, Alex Julian; Mendoza Vargas, Emma Yolanda (Editorial Grupo AEA, 2026)
The objective of this research is to evaluate the impact of technological innovation in social enterprises in the canton of Quevedo. For this purpose, field and descriptive types of research were used, using inductive and deductive methods. The study population included 125 social entrepreneurs. Data collection was carried out through surveys, interviews and direct observation. The results revealed that success in social entrepreneurship, in terms of technological innovation, is based on the principles of sustainability, significance and feasibility, encompassing both social and operational aspects. However, significant obstacles were identified, such as limited financial resources and technical knowledge, which hinder the implementation of technologies in these ventures. In addition, it became evident that the current supply of social innovation programs is insufficient and lacks quality, thus underscoring the imperative need for high quality training programs, led by professionals competent in technological innovation. In this context, it is recommended to strengthen the capacity of entrepreneurs through holistic training programs and to establish indicators that reflect the interrelation between social and operational results. The importance of providing financial support and promoting the dissemination of training programs aligned with the real technological needs of social entrepreneurs is also highlighted. These efforts should be carried out under the leadership of competent professionals and with continuous feedback mechanisms to ensure sustainable and effective development in the field of technological innovation in social entrepreneurship.